Accuracy of Doppler USG Assessment of Lower Extremity Peripheral Arterial Disease Using CTA as Gold Standard - Sarshar, Sahar; Khan, Muhammad Babar; Muhammad, Dost; Sanaullah, .; Parveen, Ishrat; Sarfaraz, Sahr (Biological and Clinical Sciences Research Journal, 2025)
Peripheral arterial disease (PAD) is a significant yet underdiagnosed vascular condition, particularly in low—and middle-income countries like Pakistan. Doppler ultrasonography (USG) is widely used as a noninvasive diagnostic tool, but its accuracy compared to computed tomography angiography (CTA)—the current gold standard—remains to be fully validated in the local context. Objective: CTA was used as the gold standard in a tertiary care hospital in Pakistan to evaluate the diagnostic accuracy of Doppler USG for detecting lower extremity PAD. Methods: This diagnostic accuracy study was conducted at Teaching Hospital Kharian from April to September 2024 and included 86 patients with clinical suspicion of PAD. Each patient underwent Doppler USG followed by CTA. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated using 2×2 contingency tables. Segmental sensitivity was also assessed. Results: Doppler USG showed a sensitivity of 95.4%, specificity of 76.2%, PPV of 92.5%, NPV of 84.2%, and an overall accuracy of 90.7% compared to CTA. Segmental analysis revealed the highest sensitivity in the femoral and popliteal arteries, with slightly reduced accuracy in tibial vessels. Three false-negative and five false-positive cases were identified. Conclusion: Doppler USG is a highly sensitive and reliable tool for diagnosing lower extremity PAD, particularly in proximal arterial segments. It can be an effective first-line imaging modality in resource-limited settings, with CTA reserved for inconclusive or complex cases.